Pengaruh Servicescape Terhadap Kualitas Pelayanan - Ferdinal, Erick; Tjahjawati, Sri Surjani (Jurnal Riset Bisnis dan Investasi, 2017)
Each company must strive to provide the best service to its customers to win the competition, thus the quality of service becomes one important. To provide good quality services to customers, the physical environment interaction between the company and the customer called with servicescape becomes a consideration. Servicescape dimensions that are measured in this study are aesthetic facilities, lighting, ambiance, layout, equipment, and employees, while for the service quality dimensions that are used in this study are tangible, reliability, responsiveness, assurance and empathy. The purpose of this study is to reveal the influence servicescape on service quality Dana Pensiun Telkom Bandung City. 125 questionnaires distributed, but the data can be taken as many as 116. The data analysis is done is descriptive analysis, regression, and hypothesis testing. Based on the research that has been done, there is a positive influence of servicescape on quality service Dana Pensiun Telkom Bandung.